mRNA Levels of MAOA and 5-HT2A Receptor in Patients With Pathological Internet Use: Correlations With Comorbid Symptoms - Qiu, Mimi; Zhang, Chenchen; Dai, Yu; Zhang, Lingrui; Wang, Yang; Peng, Wei; Chen, Yalin; Wen, Chao; Li, Hui; Zhu, Tianmin (Frontiers in Psychiatry, 2021)
Objective: Uncontrolled internet use may lead to the emergence of pathological internet use (PIU). PIU has become a global public health concern that can cause a range of psychotic symptoms, including anxiety, depression, and impulse control disorders of internet use. To date, we know very little about the principal biological factors related to PIU. Monoamine oxidase type A (MAOA) and serotonin (5-HT) 5-HT2A receptor (5-HT2AR) play critical roles in the development of behavioural and drug addictions. Thus, the aim of this study was to measure the relative expression of mRNA of MAOA and 5-HT2AR in peripheral blood mononuclear cells (PBMCs) of patients with PIU and to determine the correlations between these biological indicators and the comorbid symptoms of patients with PIU. Methods: In this study, the mRNA of MAOA and 5-HT2AR was detected using real-time PCR in PBMCs of the patients with PIU (n = 24) and healthy controls (HCs, n = 25). The relationship between the mRNA levels of MAOA and 5-HT2AR and clinical symptoms in patients with PIU were further investigated. Results: MAOA mRNA in PBMCs was significantly upregulated in patients with PIU compared with that in HCs. mRNA levels of 5-HT2AR were not found to differ significantly between HCs and patients with PIU. Correlation analyses further revealed a significantly positive correlation between the relative expression of MAOA mRNA in PBMCs of patients with PIU and the Young’s Internet Addiction Test and Self-Rating Depression Scale scores. Conclusion: The present study revealed the upregulated expression of MAOA mRNA in patients with PIU and an association between the expression of MAOA mRNA and clinical symptoms of PIU, suggesting that there may be similar neurobiological changes between PIU and substance addiction. Additionally, this study demonstrated a potential association between comorbid symptoms and mRNA levels of MAOA.